Exploring strategies to reduce moral hazard and adverse selection of Ghanaian public–private partnership (PPP) construction projects. Issue 2 (10th August 2020) - Owusu-Manu, De-Graft; Kukah, Augustine Senanu; Boateng, Frank; Asumadu, George; Edwards, David John
Abstract : Purpose: Conditions of inadequate and asymmetric information when an agent is hired by a principal have resulted in the problems of moral hazard and adverse selection (MHAS) in public–private partnership (PPP) construction projects. The purpose of this study is to explore strategies to reduce MHAS in PPP construction projects. Design/methodology/approach: Questionnaires were used to elicit responses from respondents. Mean score ranking was used to rank these strategies while reliability analysis was conducted using Cronbach's alpha coefficient and level of agreement tested using Kendall's concordance. Factor analysis grouped the strategies into eight components. Findings: From the mean score ranking, monitoring; transfer of risks; screening; managing of construction risks; and increased incentives to control costs were the most significant strategies. The eight components were transparent process and contract, incentives and monitoring, screening and technical assistance, unbundling and benchmarking, funding and small liabilities, information clarification and signaling, risk and contract management and cooperation and finance factors. Practical implications: The findings of this study have identified the most significant strategies to reduce MHAS on PPP construction projects to serve as a guide to PPP practitioners in reducing MHAS. Originality/value: The output of this research contributes to the checklist of strategies that reduce PPP project failures arising from MHAS and contributes to the development of the agency theory.